Design and Research of the Test Platform for Differential Type Stepless Speed Coupling Transmission - Liu Kai; Li Yumin; Yang Zhijun; Yin Wenqing (Jixie chuandong)
Aiming at the research of pure electric power transmission,the single low-power motor has the problems of low power,small speed range which can cause motor damage and the single high-power motor has the problem of large own load,large energy loss and other issues. A differential type parallel coupled input single output power transmission test bench is designed,the relationship between input and output speed and power loss when the load changed under different working modes is studied. The results of simulation test and the test bench test run shows,when the motor reaches steady state operation,the rated power is 0. 49 k W,the average output power is about 0. 482 k W,power loss is less than 10 W,speed range increases 29. 17%,transmission efficiency is greater than 81. 7%,output power is enhanced effectively and also has fine repeatability. The experimental research platform is provided for the further research on the dynamic optimization of the coupling transmission system.